(untitled) - Trombley, Mark A. (Boston, MA, 2003)
Accounting for Derivatives and Hedging, by Mark Trombley, is a short (250-page) supplement for Advanced Accounting and other upper level accounting courses. While many books used for these courses contain some coverage of Derivatives, professors must spend valuable time preparing their own materials in order to thoroughly cover this complex subject. Trombley's text provides the desired information and detail, allowing faculty to cover derivatives in class without a lot of prep work. Using simple but realistic examples, Trombley explains options, forwards, futures, swaps, and other types of derivatives, and helps students understand applications of derivative financial instruments
Keywords: Derivatived securities,Helging (finance); Accounting,Accounting